PWE-121 Development And Psychometric Testing Of An Inflammatory Bowel Disease Fatigue (ibd-f) Patient Self-assessment Scale. (9th June 2014) - Czuber-Dochan, WJ; Norton, C; Berliner, S; Bredin, F; Darvell, M; Forbes, A; Gay, M; Nathan, I; Ream, E; Terry, H; Bassett, P
Abstract : Introduction: Fatigue is one of the main symptoms of inflammatory bowel disease (IBD) and is frequently reported by people in both active and quiescent disease. Different fatigue assessment scales have been used to measure fatigue, but none has been developed or tested in IBD. 1 This study aimed to develop a new fatigue scale specific to the needs and experiences of people with IBD. Methods: A sequential mixed methods design was used: a qualitative phase (Phase 1) to assess patients' experience of fatigue and four mixed qualitative-quantitative phases (Phase 2–5) to refine the scale and to assess its psychometric properties. Phase 1–4 participants were purposively selected from a group of volunteers who self reported their fatigue, and participants for Phase 5 were randomly selected from the Crohn's and Colitis UK members database. Results: 567 people participated in the 5 phases. The resulting IBD-F questionnaire has 3 sections: Section 1 Fatigue Assessment; Section 2 Fatigue Impact on Daily Activities; Section 3 Additional Comments about Fatigue. Initial validation suggests that the questionnaire has good face and content validity and acceptable to excellent test-retest stability (ICC 0.74 for section 1 and 0.83 for section 2) and a high degree of internal consistency with Cronbach's alpha value of over 0.9. Conclusion: The participants in the study confirmed that fatigue in IBD is burdensome. Items generated and refined by people with IBD-fatigue reflect their experience and form the basis of this new IBD-fatigue scale, which is psychometrically robust and its reliability falls within statistically acceptable ranges. The fatigue scores obtained by the newly developed, disease specific IBD-F self-assessment scale strongly correlated with the existing fatigue scales (MFI and MAF) developed with other diseases. 2, 3 The scale can be used by patients and practitioners to assess severity and impact of fatigue in people with IBD. An electronic copy of IBD-F scale can be accessed through website link http://www.fatigueinibd.co.uk from July 2014. References: Whitehead L, The measurement of fatigue in chronic illness: a systematic review of unidimensional and multidimensional fatigue measures. J of Pain and Symptom Manag. 2009;37(1):107–28 Smets EM, et al. The Multidimensional Fatigue Inventory (MFI) psychometric qualities of an instrument to assess fatigue. J of Psychosom Research. 1995;39:315–25 Belza B, et al. Correlates of fatigue in older adults with rheumatoid arthritis. Nur Research . 1993;42(2):93–9 Disclosure of Interest: W. Czuber-Dochan Grant/research support from: Big Lottery Fund managed by Crohn's and Colitis UK, C. Norton Grant/research support from: Big Lottery Fund managed by Crohn's and Colitis UK, S. Berliner Conflict with: Trustee Crohn's and Colitis UK, F. Bredin Grant/research support from: Big Lottery Fund managed by Crohn's and Colitis UK, M. Darvell Employee of: Crohn's and Colitis UK, A. Forbes Grant/research support from: Big Lottery Fund managed by Crohn's and Colitis UK, M. Gay Conflict with: Vice-Chair and Trustee Crohn's and Colitis UK, I. Nathan Grant/research support from: Big Lottery Fund managed by Crohn's and Colitis UK, E. Ream: None Declared, H. Terry Employee of: Crohn's and Colitis UK, P. Bassett: None Declared.